Psychiatric Comorbidities in Inflammatory Bowel Disease - Larion, Sebastian; P. DeCecchis, Daniel; M. Arnold, Janet; A. Vanslyke, John; R. Tavakoli, Hamid (Current Psychiatry Reviews, 2015)
Inflammatory bowel disease (IBD) classically consists of ulcerative colitis and Crohn’s disease, which are typically characterized by progressive cyclical attacks of abdominal pain, diarrhea and fatigue. Other highly prevalent clinical features of IBD include psychiatric disorders such as mood and anxiety, which may occur in 60-80% of patients during relapse. Stressful live events seem to precipitate IBD diagnosis, and are related to a significantly increased risk of disease relapse. Alternatively, an IBD diagnosis itself is associated with an increased risk for the development of anxiety and depression. These conditions lead to significantly worsened prognosis, increased risk of relapse, increased healthcare utilization, and decreased quality of life. Risk factors known to predict anxiety and depression in patients with IBD include female gender, presence of other medical comorbidities, severe and active disease, and socioeconomic deprivation. Thus, increased clinical suspicion for comorbid mood or anxiety disorders must be made once a diagnosis of inflammatory bowel disease is established, with appropriate followup. This review summarizes the literature regarding the relationship between IBD and the development of psychiatric disorders.
Keywords: depression